The Effect of Environmental, Social, and Governance (ESG) Disclosure and Dividend Policy on Firm Value with Institutional Ownership as a Moderating Variable - Nabilah Ratnaduhita Firjatullah; Chorry Sulistyowati; Elsa Yustika Putri; Zahrin Haznina Qalby; Cicik Andria (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study aims to analyze the effect of competence, work motivation, and organizational culture on employee performance in a facility services company, PT Esefa Semesta Facility. The characteristics of work in this sector require adherence to standard operating procedures, service consistency, and adaptability to client needs. The study employed an explanatory quantitative design with a cross-sectional approach. Data were collected through structured questionnaires administered to all employees (total saPmpling), comprising 62 respondents. The analysis was conducted using multiple linear regression with SPSS version 26 after passing validity, reliability, and classical assumption tests. The results indicate that competence (B = 0.331; p = 0.010), work motivation (B = 0.284; p = 0.020), and organizational culture (B = 0.388; p = 0.010) have a positive and significant effect on employee performance. Simultaneously, the regression model is significant (F = 102.080; p < 0.001) with an Adjusted R² value of 0.833, indicating that the model explains 83.3% of the variance in employee performance. These findings confirm that strengthening job-relevant competencies, maintaining work motivation, and developing an adaptive organizational culture are essential managerial strategies to enhance performance in facility services operations, while acknowledging the limitations of causal inference due to the cross-sectional design.